In the eye of the storm…again! Social policy responses to COVID‐19 in Southern Europe. (29th December 2020) - Moreira, Amílcar; Léon, Margarita; Coda Moscarola, Flavia; Roumpakis, Antonios
Abstract: This paper aims to describe and discuss the significance of the social policy measures implemented in Southern European countries—Greece, Italy, Portugal and Spain—in response to the first wave of COVID‐19. Our analysis covers interventions from 1 March to June 30, 2020. Despite significant differences in how the COVID‐19 pandemic spread—with Italy and Spain experiencing much higher rates of infection and lethality—Southern European economies are among the most hard‐hit—and are likely to find themselves in the eye of the storm, once more. The paper shows that despite differences in how countries have countered the spread of COVID‐19, there are important commonalities in the actions governments took to counteract the economic impact of the pandemic. Foremost efforts were directed at wage subsidy schemes to contain mass job destruction, additional temporary benefits to compensate self‐employed and other non‐standard workers for the loss of earnings; the expansion of unemployment insurance; and finally, the introduction and/or strengthening of schemes to provide support to families with care responsibilities. The scale of the social policy and employment protection response has nevertheless been constrained by the fiscal position of each individual country in the post‐Euro crisis context. We argue that, in the long run, the response capacity of these governments and the social and economic consequences of this crisis will need to be contextualised against the backdrop of the deep and prolonged impact of austerity‐driven measures on public budgets, production and welfare regimes over the last decade.